A blood agar for detecting pathogen - Amin Nordin, Syafinaz; Neela, Vasantha Kumari; Awang Hamat, Rukman; Ahmadi, Shahram (2014)
The present invention relates to a a blood agar for detecting pathogen from peritoneal samples. The blood agar comprising: 8 to 12 g/L of Lemco’s powder; 8 to12 g/L of peptone; 4 to 6 g/L of sodium chloride; 13 to 17 g/L of agar-agar; and 18 to 22 mL/L of Tween 80. Advantageously, the blood agar is used in detecting pathogen rapidly, thus early and appropriate antimicrobial therapy for continuous ambulatory peritoneal dialysis (CAPD) patients.